Evaluation of abstinence motivation for people who have alcohol dependence - Kaunė, Kristina; Lukminienė, Vilma; Palinauskienė, Liucija Ramunė (Slauga. Mokslas ir praktika, 2023)
Problem. Alcohol addiction is an important problem for both society and healthcare. A lot of scientific research on the problems, conse-quences and treatment of alcohol consumption has been carried out in the world and in Lithuania, but there is a lack of deeper analysis of personal experiences related to the motivation of addicted persons, their opinion about treatment and needs. Aim of the study is to assess the motivation for sobriety of alcohol-dependent persons. Methods. A qualitative study was conducted using a semi-structured interview and analyzing the data using the qualitative content analysis method. The study participants are 6 alcohol-dependent persons who continue treatment in the psychosocial rehabilitation department during the study. Results and Conclusions. Based on the statements of the participants in the study, it was found out that it was not easy for the respondents to give up alcohol: they distanced themselves from friends who drank alcohol, they felt awkward and stupid when they had to explain why they did not drink, it was unpleasant to see drunken friends with sober eyes, it was difficult to figure out what to do, especially on weekends. The participants decided to pursue sobriety based on external and internal motivation. External motivating factors family members, relatives, colleagues, lost work and property; internal - deteriorated health, relationship problems in the family, stigmatizing society’s attitude, self-loathing.